Spatiotemporal dynamics of electrocorticographic high gamma activity during overt and covert word repetition. - Pei, Xiao-Mei; Leuthardt, E C; Charles M Gaona; Peter Brunner; Jonathan Wolpaw; Gerwin Schalk (Neuroimage, 2011)
Language is one of the defining abilities of humans. Many studies have characterized the neural correlates of different aspects of language processing. However, the imaging techniques typically used in these studies were limited in either their temporal or spatial resolution. Electrocorticographic (ECoG) recordings from the surface of the brain combine high spatial with high temporal resolution and thus could be a valuable tool for the study of neural correlates of language function. In this study, we defined the spatiotemporal dynamics of ECoG activity during a word repetition task in nine human subjects. ECoG was recorded while each subject overtly or covertly repeated words that were presented either visually or auditorily. ECoG amplitudes in the high gamma (HG) band confidently tracked neural changes associated with stimulus presentation and with the subject's verbal response. Overt word production was primarily associated with HG changes in the superior and middle parts of temporal lobe, Wernicke's area, the supramarginal gyrus, Broca's area, premotor cortex (PMC), primary motor cortex. Covert word production was primarily associated with HG changes in superior temporal lobe and the supramarginal gyrus. Acoustic processing from both auditory stimuli as well as the subject's own voice resulted in HG power changes in superior temporal lobe and Wernicke's area. In summary, this study represents a comprehensive characterization of overt and covert speech using electrophysiological imaging with high spatial and temporal resolution. It thereby complements the findings of previous neuroimaging studies of language and thus further adds to current understanding of word processing in humans.
Keywords: Adolescent; Adult; Brain; Brain Mapping; Electroencephalography; Female; Humans; Male; Middle Aged; Signal Processing, Computer-Assisted; Verbal Behavior

Evolution of brain-computer interfaces: going beyond classic motor physiology. - Leuthardt, E C; Gerwin Schalk; Roland, Jarod; Rouse, Adam; Moran, D (Neurosurg Focus, 2009)
The notion that a computer can decode brain signals to infer the intentions of a human and then enact those intentions directly through a machine is becoming a realistic technical possibility. These types of devices are known as brain-computer interfaces (BCIs). The evolution of these neuroprosthetic technologies could have significant implications for patients with motor disabilities by enhancing their ability to interact and communicate with their environment. The cortical physiology most investigated and used for device control has been brain signals from the primary motor cortex. To date, this classic motor physiology has been an effective substrate for demonstrating the potential efficacy of BCI-based control. However, emerging research now stands to further enhance our understanding of the cortical physiology underpinning human intent and provide further signals for more complex brain-derived control. In this review, the authors report the current status of BCIs and detail the emerging research trends that stand to augment clinical applications in the future.
Keywords: Brain; Cerebral Cortex; Humans; Man-Machine Systems; Motor Cortex; Movement; Movement Disorders; Neuronal Plasticity; Prostheses and Implants; Research; Signal Processing, Computer-Assisted; User-Computer Interface

A practical procedure for real-time functional mapping of eloquent cortex using electrocorticographic signals in humans. - Peter Brunner; A L Ritaccio; Lynch, Timothy M; Emrich, Joseph F; Adam J Wilson; Williams, Justin C; Aarnoutse, Erik J; Ramsey, Nick F; Leuthardt, E C; H Bischof; Gerwin Schalk (Epilepsy Behav, 2009)
Functional mapping of eloquent cortex is often necessary prior to invasive brain surgery, but current techniques that derive this mapping have important limitations. In this article, we demonstrate the first comprehensive evaluation of a rapid, robust, and practical mapping system that uses passive recordings of electrocorticographic signals. This mapping procedure is based on the BCI2000 and SIGFRIED technologies that we have been developing over the past several years. In our study, we evaluated 10 patients with epilepsy from four different institutions and compared the results of our procedure with the results derived using electrical cortical stimulation (ECS) mapping. The results show that our procedure derives a functional motor cortical map in only a few minutes. They also show a substantial concurrence with the results derived using ECS mapping. Specifically, compared with ECS maps, a next-neighbor evaluation showed no false negatives, and only 0.46 and 1.10% false positives for hand and tongue maps, respectively. In summary, we demonstrate the first comprehensive evaluation of a practical and robust mapping procedure that could become a new tool for planning of invasive brain surgeries.
Keywords: Adult; Brain Mapping; Cerebral Cortex; Electric Stimulation; Electrodes, Implanted; Electroencephalography; Epilepsy; Female; Humans; Male; Middle Aged; Practice Guidelines as Topic; Signal Processing, Computer-Assisted; Young Adult

Electrocorticographic Frequency Alteration Mapping: A Clinical Technique for Mapping the Motor Cortex. - Leuthardt, E C; Miller, John W; Nicholas R Anderson; Gerwin Schalk; Dowling, Joshua; Miller, John W; Moran, D; Ojemann, J G (Neurosurgery, 2007)
OBJECTIVE:  Electrocortical stimulation (ECS) has been well established for delineating the eloquent cortex. However, ECS is still coarse and inefficient in delineating regions of the functional cortex and can be hampered by after-discharges. Given these constraints, an adjunct approach to defining the motor cortex is the use of electrocorticographic signal changes associated with active regions of the cortex. The broad range of frequency oscillations are categorized into two main groups with respect to the sensorimotor cortex: low and high frequency bands. The low frequency bands tend to show a power reduction with cortical activation, whereas the high frequency bands show power increases. These power changes associated with the activated cortex could potentially provide a powerful tool in delineating areas of the motor cortex. We explore electrocorticographic signal alterations as they occur with activated regions of the motor cortex, as well as its potential in clinical brain mapping applications. METHODS:  We evaluated seven patients who underwent invasive monitoring for seizure localization. Each patient had extraoperative ECS mapping to identify the motor cortex. All patients also performed overt hand and tongue motor tasks to identify associated frequency power changes in regard to location and degree of concordance with ECS results that localized either hand or tongue motor function. RESULTS:  The low frequency bands had a high sensitivity (88.9-100%) and a lower specificity (79.0-82.6%) for identifying electrodes with either hand or tongue ECS motor responses. The high frequency bands had a lower sensitivity (72.7-88.9%) and a higher specificity (92.4-94.9%) in correlation with the same respective ECS positive electrodes. CONCLUSION:  The concordance between stimulation and spectral power changes demonstrate the possible utility of electrocorticographic frequency alteration mapping as an adjunct method to improve the efficiency and resolution of identifying the motor cortex.
Keywords: Adult; Biological Clocks; Brain Mapping; Electric Stimulation; Electrodes, Implanted; Electroencephalography; Female; Hand; Humans; Male; Middle Aged; Motor Cortex; Oscillometry; Signal Processing, Computer-Assisted; Tongue